Emigration and Firm Productivity: Evidence from the Sequential Opening of EU Labour Markets - Yvonne Giesing; Nadzeya Laurentsyeva (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper establishes a causal link between the emigration of skilled workers and firm performance. We exploit time, country, and industry differences in the opening of EU labour markets from 2004 to 2014 as a source of exogenous variation in the emigration rates from new EU member states. Using firm-level panel data from ten East European countries, we show that the outflow of skilled workers reduces firm total factor productivity and increases personnel costs. One explanation for this effect is the increased job turnover, which lowers firm-specific human capital. We find that the most productive firms adapt more easily to emigration as they are better able to retain and train their workers.
Keywords: F22; O15; D24; 330